Maintenance vitamin D3 dosage requirements in Chinese women with post menopausal osteoporosis living in the tropics - Venugopal, Yogeswari; Hatta, Sharifah Sharifah Faradila Wan Muhamad; Musa, Nurbazlin; Rahman, Siti Abdul; Ratnasingam, Jeyakantha; Paramasivam, Sharmila Sunita; Lim, Lee Ling; Ibrahim, Luqman; Choong, Karen; Tan, Alexander Tong Boon; Chinna, Karuthan; Chan, Siew Pheng; et al. (HEC Press, 2017)
Background and Objectives: Vitamin D3 (cholecalciferol) dose required to maintain sufficiency in non- Caucasian women with postmenopausal osteoporosis (PMO) inthe tropics has not been well studied. Some guidelines mandate 800-1000 IU vitamin D/day but the Endocrine Society (US) advocates 1500-2000 IU/day to maintain 25-hydroxyvitamin-D (25(OH)D) concentration at > 75 nmol/L. We aimed to establish oral cholecalciferol dose required to maintain 25(OH)D concentration at > 75 nmol/L in PMO Chinese Malaysian women, postulating lower dose requirements amongst light-skinned subjects in the tropics. Methods and Study Design: 90 Chinese Malaysian PMO women in Kuala Lumpur, Malaysia (2°30'N) with baseline serum 25(OH)D levels ≥ 50 nmol/L were recruited. Prior vitamin D supplements were discontinued and subjects randomized to oral cholecalciferol 25,000 IU/4-weekly (Group-A) or 50,000 IU/4-weekly (Group- B) for 16 weeks, administered under direct observation. Serum 25(OH)D, PTH, serum/urinary calcium were measured at baseline, 8 and 16 weeks. Results: Baseline characteristics, including osteoporosis severity, sun exposure (~3 hours/week), and serum 25(OH)D did not differ between treatment arms. After 16 weeks, 91% of women sufficient at baseline, remained sufficient on 25,000 IU/4-weekly compared with 97% on 50,000 IU/4-weekly with mean serum 25(OH)D 108.1±20.4 and 114.7±18.4 SD nmol/L respectively (p=0.273). At trial's end, 39% and 80% of insufficient women at baseline attained sufficiency in Group A and Group B (p=0.057). Neither dose was associated with hyperparathyroidism or toxicity. Conclusions: Despite pretrial vitamin D supplementation and adequate sun exposure, 25.6% Chinese Malaysian PMO women were vitamin D insufficient indicating sunshine alone cannot ensure sufficiency in the tropics. Both ~900 IU/day and ~1800 IU/day cholecalciferol can safely maintain vitamin D sufficiency in > 90% of Chinese Malaysian PMO women. Higher doses are required with baseline concentration < 75 nmol/L.